High-strength welded joints with improved toughness due to large heat input
By optimizing alloy compositions and electro gas welding parameters, the welding joint achieves enhanced low-temperature impact toughness and high strength by controlling ferrite and bainite phases, addressing the challenges of existing steel materials in crushed ice ships.
Patent Information
- Application Number
- JP2024537313
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-21
- Filing Date
- 2022-12-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-20
AI Technical Summary
Existing high-strength steel materials for welding joints in crushed ice ships face challenges in maintaining low-temperature impact toughness and high strength due to the increase in bainite phase and granular ferrite when large amounts of alloy elements are added, leading to reduced toughness.
The solution involves maximizing needle-shaped ferrite and minimizing granular ferrite and upper bainite phases by controlling the composition of alloy elements such as C, Mn, Si, Ni, Cr, Cu, Mo, Ti, Nb, O, N, P, and S, with a carbon equivalent (CEQ) between 0.45% and 0.50%, and performing electro gas welding at a heat input of 160 kJ/cm or more.
This approach achieves a high-strength welding joint with improved low-temperature impact toughness, tensile strength, and ductility, ensuring a surrender intensity of 500 MPa or more, tensile strength of 610 to 770 MPa, and -20°C impact toughness of 50 J or more, while maintaining high productivity.
Smart Images

Figure 2025502690000001 
Figure 2025502690000002 
Figure 2025502690000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength welded joint having improved large heat input toughness, and more particularly to a high-strength welded joint having improved large heat input toughness by controlling the microstructure. [Background technology]
[0002] In recent years, as the Arctic sea ice area is rapidly decreasing due to rising temperatures caused by global warming, interest in opening Arctic shipping routes is growing. In order to operate Arctic shipping routes, it is essential to build icebreakers that can break up the sea ice and open up shipping routes.
[0003] The steel materials used in the hulls of icebreakers must have excellent impact toughness at low temperatures and high strength to protect the hull from the impacts of icebreaking. Therefore, the steel materials and welded joints for icebreakers must be made of fine, high-strength low-temperature transformed phase structures, and large amounts of alloying elements are added to them.
[0004] Recently, shipbuilding companies have been continuously demanding steel materials and welded joints that can be used with electrogas welding to improve productivity in the construction of icebreakers. However, when a large amount of alloying elements is added, a problem occurs in that the toughness of the welded joint drops sharply due to the formation of a single bainite phase in the welded joint and heat-affected zone. Therefore, the reality is that there are almost no inventions for high-strength steel materials and welded joints for large heat input welding that can be used with electrogas welding. Summary of the Invention [Problem to be solved by the invention]
[0005] In order to solve the above problems, an object of the present invention is to provide a high-strength welded joint having improved high heat input toughness and capable of simultaneously realizing low-temperature impact toughness and high strength by maximizing the fraction of acicular ferrite and minimizing the fraction of grain boundary ferrite and upper bainite to refine the grain size, and a method for manufacturing the same. [Means for solving the problem]
[0006] The high strength welded joint with improved high heat input toughness of the present invention has, by weight, C: 0.03% or more and 0.045% or less, Mn: 1.45% or more and 1.55% or less, Si: 0.3% or more and 0.4% or less, Al: 0.02% or more and 0.03% or less, Ni: 1.55% or more and 1.70% or less, Cr: 0.05% or more and 0.07% or less, Cu: 0.05% or more and 0.08% or less, Mo: 0.14% or more and 0.2% or less, Ti: 0.06% or more and 0. 07% or less, Nb: 0.004% or more and 0.005% or less, O: 0.035% or more and 0.05% or less, N: 40 ppm or more and 180 ppm or less, P: more than 0 ppm and 80 ppm or less, S: more than 0 ppm and 90 ppm or less, with the remainder being iron (Fe) and other unavoidable impurities, and is characterized by containing, in terms of area fraction, 85% or more of acicular ferrite, 14% or less of grain boundary ferrite, and 0.1% or less of upper bainite.
[0007] Moreover, the high-strength welded joint of the present invention with improved large heat input toughness has a carbon equivalent (Ceq) represented by the following formula (1) of 0.45% or more and 0.50% or less.
[0008] Formula (1): [C]+[Mn] / 6+(Cr+Mo) / 5+(Ni+Cu) / 15
[0009] In the formula (1), C, Mn, Cr, Mo, Ni and Cu represent the content (wt %) of each component.
[0010] Furthermore, the high-strength welded joint of the present invention with improved large heat input toughness has an MA (island martensite-austenite) phase content of 0.5% or less.
[0011] Furthermore, the high-strength welded joint of the present invention with improved large heat input toughness has a yield strength of 500 MPa or more.
[0012] Moreover, the high-strength welded joint of the present invention with improved large heat input toughness has a tensile strength of 610 to 770 MPa.
[0013] Furthermore, the high-strength welded joint of the present invention with improved large heat input toughness has an elongation rate of 21% or more.
[0014] Furthermore, the high-strength welded joint of the present invention with improved high heat input toughness has a -20°C impact toughness of 50 J or more.
[0015] In addition, the manufacturing method of the present invention for a high-strength welded joint with improved high heat input toughness comprises, by weight percent, C: 0.03% or more and 0.045% or less, Mn: 1.45% or more and 1.55% or less, Si: 0.3% or more and 0.4% or less, Al: 0.02% or more and 0.03% or less, Ni: 1.55% or more and 1.70% or less, Cr: 0.05% or more and 0.07% or less, Cu: 0.05% or more and 0.08% or less, Mo: 0.14% or more and 0.2% or less, Ti: 0.06% or more and 0.07% or less, and Cu: 0.05% or more and 0.08% or less. The method is characterized in that it includes a step of electrogas welding a steel material having a carbon equivalent (Ceq) of 0.45% or more and 0.50% or less, containing Zn: 0.004% or more and 0.005% or less, O: 0.035% or more and 0.05% or less, N: 40 ppm or more and 180 ppm or less, P: more than 0 ppm and 80 ppm or less, S: more than 0 ppm and 90 ppm or less, with the remainder being iron (Fe) and other unavoidable impurities, and having a carbon equivalent (Ceq) represented by the following formula (1) of 0.45% or more and 0.50% or less.
[0016] Formula (1): [C]+[Mn] / 6+(Cr+Mo) / 5+(Ni+Cu) / 15
[0017] In the formula (1), C, Mn, Cr, Mo, Ni and Cu represent the content (wt %) of each component.
[0018] In the method of manufacturing a high-strength welded joint having improved high heat input toughness according to the present invention, the electrogas welding is carried out with a heat input of 160 KJ / cm or more. Effect of the Invention
[0019] According to the present invention, a high-strength welded joint having improved high heat input toughness and capable of simultaneously realizing low-temperature impact toughness and high strength by maximizing the fraction of acicular ferrite and minimizing the fraction of grain boundary ferrite and upper bainite to refine the grain size, and a manufacturing method thereof can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] A high strength welded joint with improved high heat input toughness according to one embodiment of the present invention has, by weight, C: 0.03% or more and 0.045% or less, Mn: 1.45% or more and 1.55% or less, Si: 0.3% or more and 0.4% or less, Al: 0.02% or more and 0.03% or less, Ni: 1.55% or more and 1.70% or less, Cr: 0.05% or more and 0.07% or less, Cu: 0.05% or more and 0.08% or less, Mo: 0.14% or more and 0.2% or less, Ti: 0.0 The steel may contain, in terms of area fraction, 85% or more of acicular ferrite, 14% or less of grain boundary ferrite, and 0.1% or less of upper bainite, with the remainder being iron (Fe) and other unavoidable impurities.
[0021] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. The following embodiments are presented to fully convey the concept of the present invention to those skilled in the art to which the present invention pertains. The present invention is not limited to the embodiments presented herein and may be embodied in other forms. In the drawings, parts that are not relevant to the description may be omitted in order to clarify the present invention, and the size of components may be somewhat exaggerated in order to facilitate understanding.
[0022] Throughout the specification, when a part is said to "comprise" a certain element, this means that it may further include other elements, not excluding other elements, unless specifically stated to the contrary.
[0023] The singular expression includes the plural expression unless the context clearly indicates otherwise.
[0024] The reasons for limiting the contents of alloying elements in the examples of the present invention will be described below. Unless otherwise specified, the units are % by weight.
[0025] The high strength welded joint portion with improved high heat input toughness according to one embodiment of the present invention has, by weight%, C: 0.03% or more and 0.045% or less, Mn: 1.45% or more and 1.55% or less, Si: 0.3% or more and 0.4% or less, Al: 0.02% or more and 0.03% or less, Ni: 1.55% or more and 1.70% or less, Cr: 0.05% or more and 0.07% or less, Cu: 0.05% or more and 0.08% or less, It is preferable that the content of Mo is 0.14% or more and 0.2% or less, Ti is 0.06% or more and 0.07% or less, Nb is 0.004% or more and 0.005% or less, O is 0.035% or more and 0.05% or less, N is 40 ppm or more and 180 ppm or less, P is more than 0 ppm and 80 ppm or less, S is more than 0 ppm and 90 ppm or less, and the remainder is iron (Fe) and other unavoidable impurities.
[0026] The C (carbon) content may be 0.03% or more and 0.045% or less.
[0027] C is an element effective in increasing material strength through solid solution strengthening. In consideration of this, C may be added in an amount of 0.03% or more. However, if the C content is excessive, the hardenability may be excessively improved and the upper bainite fraction may increase. In addition, if the C content is excessive, a large amount of island martensite phase may be generated, decreasing toughness. In consideration of this, the upper limit of the C content may be limited to 0.045%. Preferably, the C content may be 0.032% or more and 0.043% or less.
[0028] The Mn (manganese) content may be equal to or greater than 1.45% and equal to or less than 1.55%.
[0029] Mn is an effective element for improving strength by solid solution strengthening and improving hardenability so that a low-temperature transformation phase is generated. In consideration of this, Mn may be added in an amount of 1.45% or more. However, if the Mn content is excessive, the excessive increase in hardenability may promote the generation of upper bainite and island martensite in the weld heat-affected zone and base metal structure. Therefore, if the Mn content is excessive, the impact toughness may be significantly reduced. In consideration of this, the upper limit of the Mn content may be limited to 1.55%. Preferably, the Mn content may be 1.49% or more and 1.55% or less.
[0030] The content of Si (silicon) may be equal to or greater than 0.3% and equal to or less than 0.4%.
[0031] Silicon is an essential element for deoxidizing steelmaking and welded joints by precipitating dissolved oxygen in the form of slag. In consideration of this, silicon may be added in an amount of 0.3% or more. However, if the silicon content is excessive, coarse oxides may be generated, or a large amount of nonmetallic inclusions or coarse island martensite may be generated in the microstructure. In consideration of this, the upper limit of the silicon content may be limited to 0.4%. Preferably, the silicon content may be 0.34% or more and 0.4% or less.
[0032] The content of Al (aluminum) may be 0.02% or more and 0.03% or less.
[0033] Like Si, Al is an effective element for deoxidization. In consideration of this, Al may be added in an amount of 0.02% or more. However, if the Al content is excessive, coarse oxides or coarse island martensite may be generated. In consideration of this, the upper limit of the Al content may be limited to 0.03%. Preferably, the Al content may be 0.022% or more and 0.025% or less.
[0034] The Ni (nickel) content may be equal to or greater than 1.55% and equal to or less than 1.70%.
[0035] Ni is an important element for improving low-temperature impact toughness and improving strength. In consideration of this, Ni may be added in an amount of 1.55% or more. However, if the Ni content is excessive, the toughness may decrease due to the formation of upper bainite caused by an excessive increase in hardening ability. In addition, if the Ni content is excessive, the manufacturing cost may increase. In consideration of this, the upper limit of the Ni content may be limited to 1.70%. Preferably, the Ni content may be 1.57% or more and 1.69% or less.
[0036] The Cr (chromium) content may be equal to or greater than 0.05% and equal to or less than 0.07%.
[0037] Cr is an effective element for ensuring strength by improving hardenability. In consideration of this, Cr may be added in an amount of 0.05% or more. However, if the Cr content is excessive, the toughness may decrease due to the formation of upper bainite caused by an excessive increase in hardenability. Furthermore, if the Cr content is excessive, the manufacturing cost may increase. In consideration of this, the upper limit of the Cr content may be limited to 0.07%. Preferably, the Cr content may be 0.052% or more and 0.061% or less.
[0038] The content of Cu (copper) may be equal to or greater than 0.05% and equal to or less than 0.08%.
[0039] Cu is an element effective in improving strength and ensuring low-temperature toughness. In consideration of this, Cu may be added in an amount of 0.05% or more. However, if the Cu content is excessive, the manufacturing cost may increase. In consideration of this, the upper limit of the Cu content may be limited to 0.08%. Preferably, the Cu content may be 0.057% or more and 0.071% or less.
[0040] The Mo (molybdenum) content may be 0.14% or more and 0.2% or less.
[0041] Mo is an element effective in ensuring strength by improving hardenability. In consideration of this, Mo may be added in an amount of 0.14% or more. However, if the Mo content is excessive, the toughness may decrease due to the generation of upper bainite caused by an excessive increase in hardenability. In addition, if the Mo content is excessive, the manufacturing cost may increase. In consideration of this, the upper limit of the Mo content may be limited to 0.2%. Preferably, the Mo content may be 0.146% or more and 0.196% or less.
[0042] The Ti (titanium) content may be 0.06% or more and 0.07% or less.
[0043] Ti is an effective element for promoting the nucleation of intragranular acicular ferrite through the crystallization of Ti oxide (TiO2) in the welded joint. Ti is also an effective element for refining crystal grains through the precipitation of carbonitrides. In consideration of this, Ti may be added in an amount of 0.06% or more. However, if the Ti content is excessive, it may cause excessive oxide generation, thereby reducing low-temperature impact toughness. In consideration of this, the upper limit of the Ti content may be limited to 0.07%. Preferably, the Ti content may be 0.06% or more and 0.063% or less.
[0044] The Nb (niobium) content may be 0.004% or more and 0.005% or less.
[0045] Nb is an element that is effective in improving strength by combining with C and N to form Nb-based precipitates. Taking this into consideration, Nb may be added in an amount of 0.004% or more. However, if the Nb content is excessive, a large amount of island martensite may be formed in the welded joint, which may reduce toughness. Taking this into consideration, the upper limit of the Nb content may be limited to 0.005%.
[0046] The O (oxygen) content may be 0.035% or more and 0.05% or less.
[0047] O is an element that reacts with Ti in the molten weld metal to form Ti oxides. Ti oxides can play an effective role in promoting the nucleation of intragranular acicular ferrite in the weld and refining the crystal grains. In consideration of this, O may be added in an amount of 0.035% or more. However, if the O content is excessive, the impact toughness of the weld is deteriorated due to the unnecessary formation of coarse Ti oxides and other oxides. In consideration of this, the upper limit of the O content may be limited to 0.05%.
[0048] The N (nitrogen) content may be 40 ppm or more and 180 ppm or less.
[0049] N is an element that exhibits the effect of refining the grain size by precipitating TiN and preventing the growth of prior austenite grains. In consideration of this, N may be added in an amount of 40 ppm or more. However, if the N content is excessive, free nitrogen is generated, which reduces toughness and may cause cracks in the slab due to the precipitation of AlN. In consideration of this, the upper limit of the N content may be limited to 180 ppm. Preferably, N may be 90 ppm or more and 170 ppm or less.
[0050] P (phosphorus) may be more than 0 ppm and not more than 80 ppm.
[0051] P is an element that causes embrittlement at grain boundaries, so in order to improve the brittle crack propagation resistance, the upper limit of the P content may be limited to 80 ppm.
[0052] S (sulfur) may be more than 0 ppm and not more than 90 ppm.
[0053] S is an element that causes embrittlement by forming coarse inclusions, so in order to improve the propagation resistance, the upper limit of the S content may be limited to 90 ppm.
[0054] The remaining component of the present invention is iron (Fe). However, in normal manufacturing processes, unintended impurities may be inevitably mixed in from raw materials or the surrounding environment, and it is not possible to exclude them. Since any technician in normal manufacturing processes would know about these impurities, the contents of all of them are not specifically mentioned in this specification.
[0055] The high-strength welded joint with improved high heat input toughness according to an embodiment of the present invention may have a carbon equivalent (Ceq) represented by the following formula (1) of 0.45% or more and 0.50% or less.
[0056] Formula (1): [C]+[Mn] / 6+(Cr+Mo) / 5+(Ni+Cu) / 15
[0057] In formula (1), C, Mn, Cr, Mo, Ni, and Cu represent the content (wt %) of each component.
[0058] If the carbon equivalent (Ceq) is less than 0.45%, the grain boundary ferrite phase increases, which may cause a deterioration in low-temperature impact toughness, whereas if the carbon equivalent (Ceq) exceeds 0.50%, the upper bainite phase increases, which may cause a decrease in low-temperature impact toughness.
[0059] The microstructure of a high strength welded joint with improved high heat input toughness according to an embodiment of the present invention may include, by area fraction, 85% or more of acicular ferrite, 14% or less of grain boundary ferrite, and 0.1% or less of upper bainite.
[0060] In order to simultaneously secure the strength and toughness of high heat input welded joints, it is essential to make the structure finer. Therefore, it is necessary to minimize the grain boundary ferrite phase and upper bainite phase, which reduce low temperature impact toughness, and to maximize the acicular ferrite phase.
[0061] The acicular ferrite phase can be maximized by increasing the amount of titanium oxide produced. Also, the grain boundary ferrite phase and upper bainite phase can be minimized by appropriately controlling the carbon equivalent Ceq in the welding according to an embodiment of the present invention. In other words, low-temperature impact toughness and high strength can be simultaneously ensured by controlling the alloy components and manufacturing method to ensure a fine structure.
[0062] Furthermore, the MA phase must be minimized because it reduces low-temperature impact toughness. Therefore, the high-strength welded joint with improved high heat input toughness according to one embodiment of the present invention may have an MA (island martensite-austenite) phase of 0.5% or less.
[0063] The MA phase can be minimized by reducing the alloying elements that promote the formation of MA phase, such as C, Si, and Nb.
[0064] The high-strength welded joint having improved large heat input toughness according to an embodiment of the present invention may have a yield strength of 500 MPa or more and a tensile strength of 610 to 770 MPa by controlling the microstructure. Also, the high-strength welded joint having improved large heat input toughness according to an embodiment of the present invention may have an elongation of 21% or more and a -20°C impact toughness of 50 J or more.
[0065] Next, a method for producing a high-strength welded joint having improved high heat input toughness according to another embodiment of the present invention will be described.
[0066] A manufacturing method of a high strength welded joint with improved high heat input toughness according to one embodiment of the present invention has the following composition by weight: C: 0.03% to 0.045%, Mn: 1.45% to 1.55%, Si: 0.3% to 0.4%, Al: 0.02% to 0.03%, Ni: 1.55% to 1.70%, Cr: 0.05% to 0.07%, Cu: 0.05% to 0.08%, Mo: 0.14% to 0.2%, Ti: 0.06% % or more and 0.07% or less, Nb: 0.004% or more and 0.005% or less, O: 0.035% or more and 0.05% or less, N: 40 ppm or more and 180 ppm or less, P: more than 0 ppm and 80 ppm or less, S: more than 0 ppm and 90 ppm or less, with the remainder being iron (Fe) and other unavoidable impurities, and the steel material having a carbon equivalent (Ceq) represented by the following formula (1) of 0.45% or more and 0.50% or less may be subjected to electrogas welding.
[0067] Formula (1): [C]+[Mn] / 6+(Cr+Mo) / 5+(Ni+Cu) / 15
[0068] In formula (1), C, Mn, Cr, Mo, Ni, and Cu represent the content (wt %) of each component.
[0069] The component ranges of each alloy composition and the reasons for limiting the numerical values in formula (1) are as described above, and the production method will be described in more detail below.
[0070] A method for manufacturing a high strength welded joint with improved high heat input toughness according to an embodiment of the present invention may include an electrogas welding step to improve the productivity of the welded joint.
[0071] Electrogas welding may be performed with a heat input of 160 KJ / cm or more.
[0072] Generally, when a large amount of alloying elements is added, the toughness of the weld decreases when the heat input increases due to the formation of a single bainite phase in the weld joint and heat affected zone. However, in the present invention, by controlling the microstructure, it is possible to realize a weld joint with excellent toughness even with a high heat input of 160 KJ / cm or more.
[0073] The present invention will be described in more detail with reference to the following examples. However, the description of the examples is for illustrating the implementation of the present invention, and the present invention is not limited by the description of the examples. The scope of the present invention is determined by the matters described in the claims and the matters reasonably inferred therefrom.
[0074] {Example} Welded joints were produced by electrogas welding steel materials having various alloy component ranges shown in Table 1 below with a heat input of 160 KJ / cm.
[0075] [Table 1]
[0076] Table 2 below shows the carbon equivalent, the area fraction of acicular ferrite, the area fraction of grain boundary ferrite, the area fraction of upper bainite, and the area fraction of MA.
[0077] The carbon equivalent was calculated according to the following formula (1).
[0078] Formula (1): [C]+[Mn] / 6+(Cr+Mo) / 5+(Ni+Cu) / 15
[0079] In formula (1), C, Mn, Cr, Mo, Ni, and Cu represent the content (wt %) of each component.
[0080] The acicular ferrite area fraction, grain boundary ferrite area fraction, upper bainite area fraction, and MA area fraction were measured by the method of ASTM E562-11 after photographing with an optical microscope.
[0081] [Table 2]
[0082] The yield strength, tensile strength, elongation and -20°C impact toughness are shown in Table 3 below.
[0083] The yield strength, tensile strength and elongation were measured at room temperature using a Zwick / Roell ZWICK Z250 tensile tester.
[0084] The -20°C impact toughness was measured at a low temperature of -20°C using a Zwick Roell impact tester.
[0085] [Table 3]
[0086] As shown in Tables 2 and 3, Examples 1 and 2 satisfied the alloy composition, component range, formula (1), and microstructure fraction proposed in the present invention. Therefore, Examples 1 and 2 satisfied the yield strength of 500 MPa or more, the tensile strength of 610 to 770 MPa, the elongation rate of 21% or more, and the impact toughness at -20°C of 50 J or more. That is, Examples 1 and 2 simultaneously realized low-temperature impact toughness and high strength.
[0087] However, the Ni and Ti contents were low and the carbon equivalent was relatively low in Comparative Examples 1 and 2. Therefore, the grain boundary ferrite fraction was high in Comparative Examples 1 and 2, and the yield strength and tensile strength proposed in the present invention could not be met.
[0088] In addition, Comparative Example 3 had low Ni and Ti contents and was therefore inferior in yield strength, and also had a high carbon equivalent and therefore a high upper bainite fraction, which resulted in inferior impact toughness.
[0089] Moreover, Comparative Examples 4 and 5 had high carbon equivalents due to high contents of C, Mn and / or Mo. Therefore, Comparative Examples 4 and 5 had high upper bainite fractions and were poor in elongation and -20°C impact toughness. [Industrial Applicability]
[0090] According to the present invention, a high-strength welded joint having improved high heat input toughness and simultaneously realizing low-temperature impact toughness and high strength by controlling the microstructure and refining the grain size can be provided, and therefore it can be used in various industrial fields such as various home appliances.
Claims
1. In weight percent, the alloy contains C: 0.03% or more and 0.045% or less, Mn: 1.45% or more and 1.55% or less, Si: 0.3% or more and 0.4% or less, Al: 0.02% or more and 0.03% or less, Ni: 1.55% or more and 1.70% or less, Cr: 0.05% or more and 0.07% or less, Cu: 0.05% or more and 0.08% or less, Mo: 0.14% or more and 0.2% or less, Ti: 0.06% or more and 0.07% or less, Nb: 0.004% or more and 0.005% or less, O: 0.035% or more and 0.05% or less, N: 40 ppm or more and 180 ppm or less, P: more than 0 ppm and 80 ppm or less, S: more than 0 ppm and 90 ppm or less, and the remainder being iron (Fe) and other unavoidable impurities, A high-strength welded joint having improved large heat input toughness, characterized in that it contains, in terms of area fraction, 85% or more of acicular ferrite, 14% or less of grain boundary ferrite, and 0.1% or less of upper bainite.
2. 2. A high-strength welded joint having improved large heat input toughness according to claim 1, characterized in that the carbon equivalent (Ceq) represented by the following formula (1) is 0.45% or more and 0.50% or less. Formula (1): [C]+[Mn] / 6+(Cr+Mo) / 5+(Ni+Cu) / 15 (In the formula (1), C, Mn, Cr, Mo, Ni, and Cu represent the content (wt%) of each component.)
3. 2. A high-strength welded joint with improved large heat input toughness according to claim 1, characterized in that the MA (island martensite-austenite) phase is 0.5% or less.
4. 2. The high-strength welded joint having improved large heat input toughness according to claim 1, characterized in that the yield strength is 500 MPa or more.
5. 2. The high-strength welded joint with improved large heat input toughness according to claim 1, characterized in that the tensile strength is 610 to 770 MPa.
6. 2. The high-strength welded joint having improved large heat input toughness according to claim 1, characterized in that the elongation is 21% or more.
7. 2. The high-strength welded joint having improved large heat input toughness according to claim 1, characterized in that the -20°C impact toughness is 50 J or more.
8. In weight percent, C: 0.03% to 0.045%, Mn: 1.45% to 1.55%, Si: 0.3% to 0.4%, Al: 0.02% to 0.03%, Ni: 1.55% to 1.70%, Cr: 0.05% to 0.07%, Cu: 0.05% to 0.08%, Mo: 0.14% to 0.2%, Ti: 0.06% to 0.07%, Nb: 0.004% to 0.005%, O : 0.035% or more and 0.05% or less, N: 40 ppm or more and 180 ppm or less, P: more than 0 ppm and 80 ppm or less, S: more than 0 ppm and 90 ppm or less, with the remainder being iron (Fe) and other unavoidable impurities, and a carbon equivalent (Ceq) represented by the following formula (1) of 0.45% or more and 0.50% or less, the method comprising the steps of electrogas welding a steel material having an average carbon equivalent (Ceq) of 0.035% or more and 0.05% or less, N: 40 ppm or more and 180 ppm or less, P: more than 0 ppm and 80 ppm or less, S: more than 0 ppm and 90 ppm or less, and the remainder being iron (Fe) and other unavoidable impurities: Formula (1): [C]+[Mn] / 6+(Cr+Mo) / 5+(Ni+Cu) / 15 (In the formula (1), C, Mn, Cr, Mo, Ni and Cu represent the content (wt %) of each component.)
9. 9. The method for manufacturing a high-strength welded joint having improved high heat input toughness according to claim 8, wherein the electrogas welding is performed with a heat input of 160 KJ / cm or more.
Citation Information
Patent Citations
High heat input submerged-arc welding method excellent in toughness of weld metal
JP2006051515A
Welded structural steel including welded joints with high thermal shock toughness
JP2011506766A
Flux-cored arc weld metal with excellent low-temperature CTOD characteristics and steel member having this weld metal.
JP2011507707A
Welded structural steel including welded joints with excellent CTOD properties
JP2011508087A
Ultra-high-strength gas metal arc welded joints with excellent impact toughness and solid wires for manufacturing them
JP2017508876A